Advances in analytical microextraction methods towards green chemistry - Sanagi, M. Marsin; Wan Ibrahim, Wan Aini; Abu Naim, Ahmedy; See, Hong Heng; Raharjo, Yanuardi; Miskam, Mazidatulakmam; Ismail, Rabiatul Adawiah (2008)
Membrane supported liquid-phase microextraction is one of the emerging techniques in liquid-phase microextraction (LPME) system. In this system, a polypropylene membrane impregnated with an organic solvent to accommodate or protect micro-volumes of acceptor solution. This novel methodology proved to be an extremely simple, low-cost and virtually solvent-free sample-preparation technique that parallel with green chemistry principles. LPME provides a high degree of selectivity and enrichment and additionally eliminating the possibility of carry-over between runs. In addition, LPME tolerates wide pH range that makes the technique advantageous and attractive to be used in plications that would not be suitable for solid phase extraction (SPE) or solid phase microextraction (SPME). Due to the small volume of the extracting solvent, the extracted samples do not require further concentration prior to analysis and thus total analysis time is considerably decreased in comparison to traditional liquid-liquid extraction procedure. This technique is apparently favorable especially in fulfilling the green chemistry obligations.